2001
DOI: 10.1177/003435520104400404
|View full text |Cite
|
Sign up to set email alerts
|

Physical Impairments as Risk Factors for the Development of Posttraumatic Stress Disorder

Abstract: The case-control method, a retrospective design useful in studying the etiology of rare diseases, was utilized to examine the relative risk of posttraumatic stress disorder (PTSD) among individuals with six types of traumatic physical impairments. Odds ratios and associated confidence intervals were calculated for each impairment in a group of 45,320 veterans receiving medical services. Four of the six impairments were found to be risk factors for PTSD. Implications for rehabilitation counseling and research a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
41
0
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(47 citation statements)
references
References 11 publications
4
41
0
2
Order By: Relevance
“…They were patients' accumulated past traumatic events (e.g. Falger et al, 1992;Bremner et al, 1993;Davidson and Baum, 1993;Zaidi and Foy, 1994;Alonzo, 1999Alonzo, , 2000, cardiac surgery (Doerfler et al, 1994;Chessick, 1995;Götzmann and Schnyder, 2002), cardiac arrest (Ladwig et al, 1999;O'Reilly et al, 2004), and heart failure (Martz and Cook, 2001). In addition, we planned to control for length of time since patients' first MI, mental health problems prior to MI, and patients' experiences of angina and angioplasty intervention.…”
Section: Resultsmentioning
confidence: 99%
“…They were patients' accumulated past traumatic events (e.g. Falger et al, 1992;Bremner et al, 1993;Davidson and Baum, 1993;Zaidi and Foy, 1994;Alonzo, 1999Alonzo, , 2000, cardiac surgery (Doerfler et al, 1994;Chessick, 1995;Götzmann and Schnyder, 2002), cardiac arrest (Ladwig et al, 1999;O'Reilly et al, 2004), and heart failure (Martz and Cook, 2001). In addition, we planned to control for length of time since patients' first MI, mental health problems prior to MI, and patients' experiences of angina and angioplasty intervention.…”
Section: Resultsmentioning
confidence: 99%
“…Posttraumatic stress disorder (PTSD) has been observed in one third of Japanese (13) and US (11) samples between 3 and 6 months post burn, and 15% to 20% of Dutch (12) and Greek (10) samples at 1 year. PTSD was more common among Veterans Administration patients with extensive burns than among those with spinal injuries, amputations, major chest trauma, heart failure, or cardiac arrest (14). In an Australian sample, high levels of distress during a major brush fire was more strongly associated with PTSD symptoms than were sociodemographic or preexposure psychological variables (15).…”
Section: Introductionmentioning
confidence: 92%
“…The prevalence rate varied from 19% (30) to 38% (31); 19% was found in a study that assessed PTSD close to the index event (mean 9.6 months [range 3-18 months]) (30), whereas studies evaluating PTSD caseness Ͼ22 months found prevalence rates of 27% (32) and 38% (31). Although 3 studies found prevalence rates of a considerable magnitude, a case-control study looking at the risk of PTSD within various patient groups (extensive burns, spinal disorders, amputations, major chest trauma, heart failure, and cardiac arrest) did not identify SCA as a risk factor for PTSD (33).…”
Section: Scamentioning
confidence: 98%
“…CHF was associated with a 49% increase in the risk of PTSD in a case-control study of various patients groups (extensive burns, spinal disorders, amputations, major chest trauma, CHF, and cardiac arrest) (33). However, the study was conducted in a veteran population, which limits the ability to generalize the results.…”
Section: Chfmentioning
confidence: 99%